Rancang Bangun Aplikasi Pengelolaan Hak Kekayaan Intelektual Berbasis Web (Studi Kasus Sentra HKI Universitas Muhammadiyah Surabaya) - Nugraha, Driantama Edya; Sagirani, Tri; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2019)
The Sentra HKI is one of the institutions or bureaus at the Muhammadiyah University of Surabaya which has several activities that include the management of Intellectual Property Rights (IPR). The Sentra HKI is still not fully utilizing this problem, among others, the application process is still done manually, there is no history submitted, and there is no process. This IPR Management application can be a solution to this problem. Applicants can make requests wherever and whenever, the existence of a request history for the registration process, and the assessment process with points that have been obtained from calculations using the Analytical Hierarchy Process (AHP) method. Keywords: Management, Intelectual Property Rights, Analytical Hierarchy Process